Tuberculosis in indigenous children in the Brazilian Amazon - Caroline Gava; Jocieli Malacarne; Diana Patrícia Giraldo Rios; Clemax Couto Sant'Anna; Luiz Antônio Bastos Camacho; Paulo Cesar Basta (Universidade de São Paulo, 2013)
OBJECTIVE: Assess the epidemiological aspects of tuberculosis in Brazilian indigenous children and actions to control it. METHODS: An epidemiological study was performed with 356 children from 0 to 14 years of age in Rondônia State, Amazon, Brazil, during the period 1997-2006. Cases of TB reported to the Notifiable Diseases Surveillance System were divided into indigenous and non-indigenous categories and analyzed according to sex, age group, place of residence, clinical form, diagnostic tests and treatment outcome. A descriptive analysis of cases and hypothesis test (χ²) was carried out to verify if there were differences in the proportions of illness between the groups investigated. RESULTS: A total of 356 TB cases were identified (125 indigenous, 231 non-indigenous) of which 51.4% of the cases were in males. In the indigenous group, 60.8% of the cases presented in children aged 0-4 years old. The incidence mean was much higher among indigenous; in 2001, 1,047.9 cases/100,000 inhabitants were reported in children aged < 5 years. Pulmonary TB was reported in more than 80% of the cases, and in both groups over 70% of the cases were cured. Cultures and histopathological exams were performed on only 10% of the patients. There were 3 cases of TB/HIV co-infection in the non-indigenous group and none in the indigenous group. The case detection rate was classified as insufficient or fair in more than 80% of the indigenous population notifications, revealing that most of the diagnoses were performed based on chest x-ray. CONCLUSIONS: The approach used in this study proved useful in demonstrating inequalities in health between indigenous and non-indigenous populations and was superior to the conventional analyses performed by the surveillance services, drawing attention to the need to improve childhood TB diagnosis among the indigenous population.